Kazakh “free women” grit—Chinese Kazakh women's clothing image in the context of multicultural integration of silk road - Xu, Rui (Frontiers in Psychology, 2022)
In recent years, Chinese clothing cultural heritage and knowledge genealogy along the Silk Road has become the research headline attracting public attention. Thus, Kazakh clothing in Northwestern China has become the focus of today's traditional national culture. Kazakh, located at the intersection of the Silk Road, has an important position. The traditional clothing made by various social factors reflects the style and identity integration throughout history in cultures along the Silk Road, taking women clothing as an example. Kazakh women are good at craft, which reflect their strong grit, and gradually change their role and traditional values, then guide their social role. At the same time, it reflects the awakening of Kazakh women's feminist consciousness to a large extent, and complies with the Confucianism, along with the mainstream value of "advanced gender culture" of the world's outstanding civilization achievements. This paper summarizes the form, color, and decoration of Kazakh women's clothing by analyzing the garment, headdress and footwear in Xinjiang Uygur Autonomous Region Museum, Aksai Kazakh National Museum and Capital Museum of China. Through the analysis, this paper further probes into the multicultural integration between Kazakh and the regions along the Silk Road and interprets the idea represented by the forms, colors, and decoration in the clothing to promote the inheritance and development of traditional culture and regional culture with ethical features along the Silk Road.